IMPORTANCE OF PROGRAMMING AND PRODUCTION CONTROL (PCP) IN THE PEANUT PROCESSING INDUSTRY - de Lima Tomaz, Gilsimar; Alberto Claudio Pandolfi , Marcos (Revista Interface Tecnológica, 2023)
Currently companies seek continuous quality processes and a constant improvement in productivity to achieve their goals, organizations look for manufacturing strategies, sophisticated production systems and performance indicators to eliminate any activity that does not bring value to the product or service always maintaining quality at a reduced cost. In this context, PCP plays a key role in the pursuit of operational efficiency, cost reduction, increased productivity and, ultimately, customer satisfaction. It involves the application of various techniques and tools, such as the use of information systems, demand forecasting methods, production scheduling techniques and inventory management strategies. In addition, the PCP is linked to other departments of the organization, such as sales, purchasing and quality control, ensuring effective coordination. This work will bring a study on the PCP showing all the areas that it operates, its main tools, its importance and advantages in the organization through a field research in the grain company in the region of the city of Taquaritinga-SP.